2013
DOI: 10.1111/opo.12091
|View full text |Cite
|
Sign up to set email alerts
|

Developments in the correction of presbyopia I: spectacle and contact lenses

Abstract: Purpose: To outline the refractive problems associated with presbyopia and to review the basis and relative merits of currently-available methods for their correction, with detailed consideration of spectacle and contact lens approaches. Contents: In the developed world, most of the present population will spend roughly half their lives as presbyopes. The well-known presbyopic changes with age in amplitude of accommodation and required near addition are briefly reviewed, together with the less widely acknowled… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
139
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(143 citation statements)
references
References 137 publications
(280 reference statements)
2
139
0
2
Order By: Relevance
“…MCLs demonstrated to be a good choice as they provide good visual quality [18,21,22] the desired independency from spectacles and, no less important, the aesthetic benefit (desirable mostly by women). Despite all the reported benefits, the prescription rate is still quite low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MCLs demonstrated to be a good choice as they provide good visual quality [18,21,22] the desired independency from spectacles and, no less important, the aesthetic benefit (desirable mostly by women). Despite all the reported benefits, the prescription rate is still quite low.…”
Section: Discussionmentioning
confidence: 99%
“…From these epidemiological data and considering that the most prevalence condition related with ageing is presbyopia [16], there are many patients worldwide in which both presbyopia and DED co-exist. Currently, multifocal contact lenses (MCLs) [17,18] and multifocal intraocular lenses (IOLs) [19] are both well-established and an effective way to compensate the presbyopia, reducing spectacle dependency. The ocular surface changes related to ageing may adversely affect the optical quality of the eye and could have a detrimental effect on the success of these treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it causes the diminishing of vision-targeted life quality and occupational performance of many people over 40. [1][2][3][4][5] The physiopathology of presbyopia is not clearly known. However, it has been demonstrated that various factors including the hardening of the lens, changes in the elasticity of the lens capsule, lens dimension, geometry of zonular attachments and ciliary muscle contraction may be responsible for the accommodative loss in presbyopia.…”
mentioning
confidence: 99%
“…In the accommodated eye, the forward and inward movement of the ciliary muscle allows the tension fiber system to take up the tractional forces from the posterior ZF and releases the tension in the anterior ZF; both the thickness and refractive power of the lens increase. [3][4][5] There are some surgical modalities including refractive lens exchange, mono-vision laser-assisted in situ keratomileusis (LASIK), blended vision LASIK, multifocal or accommodating intraocular lens (IOL) implantations and corneal inlay implantation for the treatment of presbyopia.4-7 Nonsurgical treatments for presbyopia include the use of near-glasses and contact lenses.5 Nowadays, otorities are speculating about topical parasympathomimetic drop treatment for pharmacological control of presbyopia, which is a nonsurgical option for the vast majority of people with near vision spectacle dependence over 40 years old. …”
mentioning
confidence: 99%
See 1 more Smart Citation